2017
DOI: 10.1177/0047239516661713
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges for Teaching Successful Online Courses in Higher Education

Abstract: Online education changes all components of teaching and learning in higher education. Many empirical studies have been conducted to examine issues in delivering online courses; however, few have synthesized prior studies and provided an overview on issues in online courses. A review of literature using Cooper’s framework was conducted to identify such issues. Three major categories of findings were identified: issues related to online learners, instructors, and content development. Learners’ issues included le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
754
1
25

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 806 publications
(804 citation statements)
references
References 56 publications
24
754
1
25
Order By: Relevance
“…This finding supports other researchers (Cheng, Pare, Collimore, & Joordens, 2011;Davies & Graff, 2005;Romero et al, 2013) who found that participation in online discussion forums are related to students' final grade. However, participation is too complex to be judged on only the quantity of discussion board posts (Kebritchi et al, 2017). The quality of interaction is important and is difficult to determine, especially as it may be different for different students (Anderson, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports other researchers (Cheng, Pare, Collimore, & Joordens, 2011;Davies & Graff, 2005;Romero et al, 2013) who found that participation in online discussion forums are related to students' final grade. However, participation is too complex to be judged on only the quantity of discussion board posts (Kebritchi et al, 2017). The quality of interaction is important and is difficult to determine, especially as it may be different for different students (Anderson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some students downloaded and saved the PDF on their personal devices, resulting in the LMS not being able to capture the usage data related to the PDF Study Guide. Online students have more control over their learning and learning materials, but to be successful in their learning the students have to be self-motivated and self-directed (Kebritchi et al, 2017). Self-directed learning can be facilitated in an online education through the design of the learning environment (Loyens, Magda, & Rikers, 2008) by providing choice and control.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons for this could be the point that LMS may not have been organised in the current way at that time, and this fact has caused this aspect not to be noticeable in these studies. Meanwhile, nowadays one of the tasks of e-teachers is to prepare content and learning activities, and to provide timely appropriate feedback (Kebritchi, Lipschuetz, and Santiague 2017). Feedback in e-learning is a very important factor in enabling students to monitor and improve their own performance (Yengin et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Concerns expressed in this study regarding the limited technological skills are congruent with Knowles' [10] theoretical assumption of the learner experience, and other studies that frequently report similar technological concerns from stemming from an online course. [21][22][23] Congruent with the literature, Millennials are comfortable with technology as they grew up with instantaneous communication in the form of email and text messages. Whereas the Generation Xers, while they used technology, their communication methods differ.…”
Section: Discussionmentioning
confidence: 99%